Impressive crowd @ CMLHS booth - Marziah, Ramli; Sarah, Zulkiple (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
5 Oct 2001. Centre for Modern Languages & Human Sciences (CMLHS) was honoured with an official visit by the Deputy Minister II of the Ministry of Higher Education (MOHE), YB Dato' Saifuddin Abdullah during the Academic Carnival 2009. Accompanying YB Dato' Saifuddin Abdullah on his visit were the Vice Chancellor, YH Professor Dato' Dr Daing Mohd Nasir Ibrahim, Deputy Vice Chancellor (Academic & Internationalization) YH Professor Dato' Dr Sabarudin Mohd and the Dean, Professor Dr Abd Jalil Borham. YB Dato' Saifuddin Abdullah was given a warm welcome by CMLHS associates as he joined the impressive crowd at CMLHS main gallery, their "Short Video Competition" booth and the "Innovative Invention Exhibition" booth. During his visit, YB Dato' Saifuddin showed keen interest with the short videos prepared by the contestants and the innovative inventions demonstrated by groups of UMP students. It was also a great honour for CMLHS staff and the participants as YB Dato' Saifuddin was pleased to receive a copy of compilation of the short videos.